When Self-View Is at Stake: Responses to Ostracism Through the Lens of Self-Verification Theory. (September 2017) - Xu, Erica; Huang, Xu; Robinson, Sandra L.
We examined the conditions under which workplace ostracism promotes prosocial reactions (i.e., helping behavior) and deters antisocial behavior (i.e., social loafing). Using data from 213 employees and their direct supervisors, we found that when group identification is strong, workplace ostracism increases the helping behavior and decreases the social loafing of employees. Moreover, we found that employees' tenure further moderates this effect; for those employees who have a strong group identification and long tenure, the positive association of ostracism and helping behavior is the strongest.